Space-Confined Effect One-Pot Synthesis of γ-AlO(OH)/MgAl-LDH Heterostructures with Excellent Adsorption Performance - Zheng, Guoyuan; Wu, Caihong; Wang, Jilin; Mo, Shuyi; Zou, Zhengguang; Zhou, Bing; Long, Fei (Nanoscale research letters, 2019)
Herein, γ-AlO(OH) as an inorganic was successfully inserted into MgAl-LDH layer by a one-pot synthesis, the composite as an adsorbent for removing methyl orange (MO) from wastewater. The structure and adsorption performance of γ-AlO(OH)/MgAl-LDH were characterized. The research shows that the expansion (003) plane and the hydroxyl active site of γ-AlO(OH)/MgAl-LDH can promote adsorption capacity and adsorption kinetics, respectively. Therefore, γ-AlO(OH)/MgAl-LDH exhibits a super adsorption performance, which completely adsorbs MO at the concentration of 1000 mg g −1 . In addition, the maximum adsorption capacity of MO was 4681.40 mg g −1 according to the Langmuir model. These results indicate that γ-AlO(OH)/MgAl-LDH is a potential adsorbent for the removal of organic dyes in water.